2023
DOI: 10.3847/1538-4357/acaea9
|View full text |Cite
|
Sign up to set email alerts
|

Precision Modeling of JWST's First Cluster Lens SMACS J0723.3–7327*

Abstract: Exploiting the fundamentally achromatic nature of gravitational lensing, we present a lens model for the massive galaxy cluster SMACS J0723.3−7323 (SMACS J0723; z = 0.388) that significantly improves upon earlier work. Building on strong-lensing constraints identified in prior Hubble Space Telescope (HST) observations, the mass model utilizes 21 multiple-image systems, 17 of which were newly discovered in Early Release Observation data from the JWST. The resulting lens model maps the cluster mass distribution … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 80 publications
0
34
0
Order By: Relevance
“…The first JWST observations of massive galaxy clusters have revealed exceptionally rich background patterns of strongly lensed galaxies, thanks to a revolutionary combination of angular resolution, depth and near-and mid-infrared coverage (e.g., Caminha et al 2022;Pascale et al 2022;Mahler et al 2023). Several JWST survey programs have targeted cluster fields to exploit the gravitational lensing magnification, in the effort to unveil primordial star-forming systems and study their physical properties (e.g., Bezanson et al 2022;Treu et al 2022;Willott et al 2022;Windhorst et al 2023).…”
Section: Introductionmentioning
confidence: 99%
“…The first JWST observations of massive galaxy clusters have revealed exceptionally rich background patterns of strongly lensed galaxies, thanks to a revolutionary combination of angular resolution, depth and near-and mid-infrared coverage (e.g., Caminha et al 2022;Pascale et al 2022;Mahler et al 2023). Several JWST survey programs have targeted cluster fields to exploit the gravitational lensing magnification, in the effort to unveil primordial star-forming systems and study their physical properties (e.g., Bezanson et al 2022;Treu et al 2022;Willott et al 2022;Windhorst et al 2023).…”
Section: Introductionmentioning
confidence: 99%
“…In what follows, we provide an overview of the final candidates and their physical properties obtained by spectral energy distribution (SED) and morphological analyses. For those in the cluster field, magnification factors are estimated by taking the median value of various lens models (Jullo et al 2007;Oguri 2010;Caminha et al 2022;Mahler et al 2023) at the position of each source. In Figure 3, we show postage stamps of the final color-cut samples.…”
Section: Resultsmentioning
confidence: 99%
“…WDF-P-949 and WDF-P-963 are treated as a single system in the main text (Section 4.1.2). a Median magnification of various lens models (Jullo et al 2007;Oguri 2010;Caminha et al 2022;Mahler et al 2023) Among the color-cut objects identified in the cluster field, ZD3, HD2, and HD3p were not detected in the public photometric catalog by the RELICS team. 8 ZD1 and ZD2 are detected and listed in the catalog (with their IDs 62 and 75) but with photometric redshift of z ∼ 1.6 and 2.0.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Space-based telescopes HST and JWST have high spatial resolution and thus enable the construction of robust lens models. Recent studies of strong lensing systems using HST and JWST (e.g., Rivera-Thorsen et al 2019;Claeyssens et al 2023;Mahler et al 2023;Wu et al 2023) were able to discern morphology and star formation at the smallest scales. Furthermore, in this redshift interval, all of the rest-frame optical nebular emission lines fall in the JWST NIRSpec bandpass.…”
Section: Discussion and Future Workmentioning
confidence: 99%